Cloud storage security : a practical guide - Wheeler, Aaron; Winburn, Michael (Amsterdam, Netherlands : Elsevier, 2015)
Cloud Storage Security: A Practical Guide introduces and discusses the risks associated with cloud-based data storage from a security and privacy perspective. Gain an in-depth understanding of the risks and benefits of cloud storage illustrated using a Use-Case methodology. The authors also provide a checklist that enables the user, as well as the enterprise practitioner to evaluate what security and privacy issues need to be considered when using the cloud to store personal and sensitive information.
2.4.2.7 Conclusion2.5 Health Apps; 2.5.1 Background; 2.5.2 Case Studies; 2.5.2.1 Security Concepts; 2.5.2.2 Questions; 2.5.2.3 Efficacy and Oversight; 2.5.2.4 Privacy and Security; 2.5.2.5 Conclusion; 2.6 Summary; References; 3 Privacy Challenges; 3.1 Who Wants Your Data?; 3.2 Privacy and Security Incidents in the News; 3.3 Legal Issues; 3.3.1 Travel; 3.3.2 Location, Location, Location; 3.3.3 Employers and Insurance Companies; 3.3.4 Litigation and e-Discovery; 3.3.5 Law Enforcement; 3.3.6 Lifestyle and Psychological Profiling; 3.4 Criminals, Authoritarian Governments, and Friends.
Includes bibliographical references.
Vendor-supplied metadata.
Keywords: Cloud computing -- Security measures; Data protection; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Data protection; Electronic books; Electronic book